ROLE OF CD8+ TUMOUR-INFILTRATING LYMPHOCYTES IN PREDICTING REGIONAL LYMPH NODE METASTASIS IN LIP AND ORAL CAVITY SQUAMOUS CELL CARCINOMA - Sukhera, Zainab Asif; Nadeem Zafar,; Nighat Ara,; Saadia Muneer,; Azka Haroon,; Saeed, Zunaira (Journal of Ayub Medical College Abbottabad, 2023)
Background: Lip and oral squamous cell carcinoma maintains a significant disease burden in Pakistan. The latest research on cancer focuses more on the role of body's immune response in tumour progression and spread rather than on the nature of neoplastic cells. Tumour-infiltrating lymphocytes constitute a major part of tumour microenvironment and infiltration of tumour stroma by cytotoxic T-cells are known to limit the tumour progression in various malignancies, such as, colorectal and stomach cancers. In our study, we aim to establish the prognostic role of CD8+ tumour-infiltrating lymphocytes in lip and oral squamous cell carcinoma. Methods: Clinico-pathological data and paraffin-embedded blocks were obtained for 100 cases of lip and oral squamous cell carcinoma. These cases were selected through non-probability, convenience sampling at the Histopathology department of A.F.I.P., Rawalpindi. Fresh sections from the tumour proper were taken and CD8 immuno-marker was applied. Data was recorded, entered and analyzed with S.P.S.S. version 27.0 and Microsoft Excel. Qualitative variables were represented as frequency/percentages and quantitative variables were represented as mean and standard deviation. Chi-squared test was applied to test association between categorical data. A p-value of <0.05 was taken as significant. Results: Increased CD8 T.I.L. density was significantly associated with pN stage (p-value= .000) and early clinical stage (p-value= .014). No significant association with other clinico-pathological parameters was established. Conclusion: CD8 T.I.L. density is a reliable marker for predicting absence or presence of cervical nodal metastasis in lip and oral S.C.C. Its predictive role in determining overall survival rate should be evaluated in future studies.